High frequency oscillations are associated with cognitive processing in human recognition memory - Kucewicz, Michal T; Cimbalnik, Jan; Matsumoto, Joseph Y; Brinkmann, Benjamin H; Bower, Mark R; Vasoli, Vincent; Sulc, Vlastimil; Meyer, Fred; Marsh, W R; Stead, S M; Worrell, Gregory A (Brain, 2014)
High frequency oscillations are associated with normal brain function, but also increasingly recognized as potential biomarkers of the epileptogenic brain. Their role in human cognition has been predominantly studied in classical gamma frequencies (30-100 Hz), which reflect neuronal network coordination involved in attention, learning and memory. Invasive brain recordings in animals and humans demonstrate that physiological oscillations extend beyond the gamma frequency range, but their function in human cognitive processing has not been fully elucidated. Here we investigate high frequency oscillations spanning the high gamma (50-125 Hz), ripple (125-250 Hz) and fast ripple (250-500 Hz) frequency bands using intracranial recordings from 12 patients (five males and seven females, age 21-63 years) during memory encoding and recall of a series of affectively charged images. Presentation of the images induced high frequency oscillations in all three studied bands within the primary visual, limbic and higher order cortical regions in a sequence consistent with the visual processing stream. These induced oscillations were detected on individual electrodes localized in the amygdala, hippocampus and specific neocortical areas, revealing discrete oscillations of characteristic frequency, duration and latency from image presentation. Memory encoding and recall significantly modulated the number of induced high gamma, ripple and fast ripple detections in the studied structures, which was greater in the primary sensory areas during the encoding (Wilcoxon rank sum test, P = 0.002) and in the higher-order cortical association areas during the recall (Wilcoxon rank sum test, P = 0.001) of memorized images. Furthermore, the induced high gamma, ripple and fast ripple responses discriminated the encoded and the affectively charged images. In summary, our results show that high frequency oscillations, spanning a wide range of frequencies, are associated with memory processing and generated along distributed cortical and limbic brain regions. These findings support an important role for fast network synchronization in human cognition and extend our understanding of normal physiological brain activity during memory processing.
Keywords: gamma oscillations; Cerebrum; Amygdala; mozková kůra; paměť; Adult; Somatosensory Cortex; Electrodes, Implanted; Affect; Cerebral Cortex; Male; Functional Neuroimaging; high frequency oscillations; lidé; memory; funkční zobrazování neurálních procesů; rozpoznávání (psychologie); lidé středního věku; Humans; mozkové vlny; nervová síť; Middle Aged; velký mozek; Electroencephalography; Young Adult; cognitive processing; elektroencefalografie; Recognition, Psychology; Hippocampus; Brain Waves; hipokampus; mužské pohlaví; Memory; somatosenzorické korové centrum; dospělí; implantované elektrody; Mental Recall; zraková percepce; mladý dospělý; neural networks; rozpomínání; amygdala; ženské pohlaví; Female; Nerve Net; Visual Perception; afekt